Nastanak i razvoj civilnog društva u postdejtonskoj Bosni i Hercegovini / Establishment and Development of Civil Society in Post-Dayton Bosnia and Herzegovina: Empirijsko istraživanje / Empirical Research - Hodžić, Muamer (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
The paper presents the results of empirical research that includes the opinions and attitudes of citizens, members of civil society organizations, as well as representatives of the municipal, city, cantonal, entity, state and government of District Brčko of B&H, civil society organizations and civil society in general in post-Dayton Bosnia and Herzegovina. The research sample is 670 respondents, who cover three target groups: citizens, elected representatives of authorities on all levels in B & H and representatives of civil society. The research was conducted in two phases in the period from September 2014 until May 2016. After the presentation of research methodology, analysis and presentation of results of empirical research, based on the subject and goal of the research, this paper gives a conclusion about the establishment and development of civil society in post-Dayton B & H, as well as 10 recommendations for further development of civil society in Bosnia and Herzegovina.